2012
DOI: 10.3724/sp.j.1263.2011.00258
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism-associated coronary spasm: A case of non-ST segment elevation myocardial infarction with thyrotoxicosis

Abstract: Hyperthyroidism is associated with many heart diseases. Thyrotoxic state has a relationship with coronary spasm. We present a case of a non-menopausal woman with hyperthyroidism who complained of chest pain. The diagnosis of coronary spasm was confirmed by coronary angiography (CAG). She is treated well with anti-thyrotoxicosis and anti-anginal medication. We recommend not use CAG as the first diagnostic choice among the patients with medication-uncontrolled hyperthyroidism and chest pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“… 6 Higher levels of prothrombotic factors and lower levels of anticoagulative factors have been demonstrated among patients with a history of thyroid cancer receiving TSH-suppressive L-thyroxine therapy in comparison the same subjects in hypothyroid phase prior to radioiodine whole-body scanning procedure. 6 Homoncik et al, reported raised concentrations of von-Willibrand factor (vWF) and increased baseline platelet plug formation in patients with thyrotoxicosis which were corrected by treatment of thyrotoxicosis with thionamides. 7 Vasospastic angina secondary to transient coronary vasospasm occurs in up to 20% of hyperthyroid patients, yet is difficult to confirm.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Higher levels of prothrombotic factors and lower levels of anticoagulative factors have been demonstrated among patients with a history of thyroid cancer receiving TSH-suppressive L-thyroxine therapy in comparison the same subjects in hypothyroid phase prior to radioiodine whole-body scanning procedure. 6 Homoncik et al, reported raised concentrations of von-Willibrand factor (vWF) and increased baseline platelet plug formation in patients with thyrotoxicosis which were corrected by treatment of thyrotoxicosis with thionamides. 7 Vasospastic angina secondary to transient coronary vasospasm occurs in up to 20% of hyperthyroid patients, yet is difficult to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary events occur 2.6 times more frequently in the presence of high free triiodothyronine levels as compared to normal levels [ 4 ]. Reported cardiac events in this setting include myocardial ischemia, angina, arrhythmia, congestive heart failure and sudden death [ 1 , 5 ]. Proposed hypotheses consist of significant underlying atherosclerosis of the coronaries, overactive sympathetic system, coronary embolization, direct damage to the coronaries and disruption of the blood supply to oxygen demand [ 1 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous reports do not support the use of coronary angiography as a first diagnostic test in patients presenting with chest pain with underlying uncontrolled hyperthyroidism because iodine containing agents (e.g. those used in coronary angiography) have the potential to induce thyrotoxicosis [ 1 , 5 ]. Thyrotoxicosis induced vasospasm can occur at any time of day which differentiates it from variant angina-related vasospasm that typically occurs in the morning [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations